RANCANG BANGUN APLIKASI KONVERSI FILE EXCEL KE FILE KML BERBASIS WEB - Diah A.P, Zahwa; Saputra, Muh. Tegar; Nurfadilah, A’tika; Efendi, Ilham Julian (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
Telkom STO (Automatic Telephone Center) 1 Kendari is one of the communication devices owned by PT. Indonesian Telecommunication to connect or distribute data from one area to another. The AOD (Access Optima and Daman) division is a division which in some of its activities uses the Google Earth application to view data, one of which is the distribution of ODP (Optical Distribution Point), but in its use there are still many obstacles that make these activities not run smoothly like the process Moving data from Excel to KML format takes a lot of time because the conversion system used is still incomplete, so some data has to be managed manually. Therefore, it is necessary to have a computerized application so that the implementation of activities related to transferring data from Excel to KML can run well and can be used by various parties in real time. This application was created using the PHP programming language with MySQL as the database and the Waterfall method for development because this development model takes a systematic and sequential approach so that the development process can be completed more easily and quickly. Application testing was carried out by application testing in the form of a trial from Telkom STO 1 which went well.